2014
DOI: 10.1051/matecconf/20141304021
|View full text |Cite
|
Sign up to set email alerts
|

Effective Duration of Gas Nitriding Process on AISI 316L for the Formation of a Desired Thickness of Surface Nitrided Layer

Abstract: Abstract. High temperature gas nitriding performed on AISI 316L at the temperature of 1200°C. The microstructure of treated AISI 316L samples were observed to identify the formation of the microstructure of nitrided surface layer. The grain size of austenite tends to be enlarged when the nitriding time increases, but the austenite single phase structure is maintained even after the long-time solution nitriding. Using microhardness testing, the hardness values drop to the center of the samples. The increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Besides that, according to the graph, it can be seen that the hardness decreases progressively as the depth increases until it approaches hardness values to those of the untreated sample. The increase in hardness as a result of the gas nitriding process has been reported previously by Mahmoud et al [66], where they found that the AISI 316L after the nitriding process have greater microhardness than compared to the untreated sample. A value surface hardness of about 1400 HV0.025 of the AISI 316L during nitrocarburizing has also been reported by Pinedo et al [67].…”
Section: Surface Hardness Profilesupporting
confidence: 77%
“…Besides that, according to the graph, it can be seen that the hardness decreases progressively as the depth increases until it approaches hardness values to those of the untreated sample. The increase in hardness as a result of the gas nitriding process has been reported previously by Mahmoud et al [66], where they found that the AISI 316L after the nitriding process have greater microhardness than compared to the untreated sample. A value surface hardness of about 1400 HV0.025 of the AISI 316L during nitrocarburizing has also been reported by Pinedo et al [67].…”
Section: Surface Hardness Profilesupporting
confidence: 77%
“…Low hardness of the surface could lead to the failure of operational parts and to the operational equipment which significantly limits the use of those materials. Therefore, one of the approaches to overcome those limitations has become a nitriding treatment [1]. Gas nitriding is a thermal treatment process for diffusing nitrogen into steels by introducing ammonia (NH3) gas in a furnace and holding at a temperature below the austenite range.…”
Section: Introductionmentioning
confidence: 99%